Individual differences in the interleukin-6 response to maximal and submaximal exercise tasks - Edwards, K. M.; Burns, V. E.; Ring, C.; Carroll, D. (Journal of Sports Sciences, 2006)
The inflammatory responsive cytokine interleukin-6 (IL-6) helps regulate immune responses to exercise. Evidence suggests that increases in IL-6 are related to exercise duration and intensity. However, the moderating effect of sex and underlying mediators have received limited attention. We compared plasma IL-6 responses to two cycling tasks with a resting control in young male (n = 12) and female (n = 12) recreationally active adults. Both 45 min tasks comprised an incremental test, either maximal or submaximal, followed by steady-state exercise at 55% peak power output. Interleukin-6 was elevated above baseline immediately after the maximal but not the submaximal task. Compared with the control condition, IL-6 was increased at 30 and 60 min after both exercise tasks. The IL-6 response was greater in women than men at 60 min after maximal exercise. Cortisol increased in both tasks compared with the control condition, the increase being greater after maximal than submaximal exercise. No associations were found between IL-6 responses and cortisol, heart rate, fitness or body mass index. The results show that 45 min of moderate-intensity exercise can increase IL-6 and suggest that the inclusion of maximal effort may accelerate this response. The finding that women showed a greater IL-6 response to maximal exercise may reflect a gender dimorphism in the immune response to stress.